A Lightweight Technique to Identify Equivalent Mutants - Souza, Beatriz; Gheyi, Rohit (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e Prática, 2020)
Mutation analysis is a popular but costly approach to assess the quality of test suites. Equivalent mutants are useless and contribute to increase costs. We propose a lightweight technique to identify equivalent mutants by proving equivalences with Z3 in the context of weak mutation testing. To evaluate our approach, we apply our technique for 40 mutation targets (mutations of an expression or statement) and automatically identify 13 equivalent mutations for seven mutation targets. We manually confirm that the equivalent mutants detected by our technique are indeed equivalent. Moreover, we evaluate our approach in the context of strong mutation testing against mutants generated by MuJava for 5 projects. Our technique detects all equivalent mutants detected by TCE. The results of our technique can be useful to improve mutation testing tools by avoiding the application of 13 mutations for 7 mutation targets.